Estimation of body weight of Maasai Zebu calves and their crosses with Sahiwal and Boran in Kajiado District, Kenya - Karimi, S.K.; Gitau, G.K.; McDermott, John J.; Kinuthia, R.N.; Gathuma, J.M. (2005)
A study that was carried out to identify calf variables that could be used to develop a simple linear regression equation for estimating body weight of calves in pastoral systems is described. The study which was carried out between November 2000 and March 2001 used 232 calves less than 10 months old from 23 Maasai households in Kajiado District. The linear regression equation obtained was significantly affected by factors such as heart girth, sex, body condition score and breed. The overall coefficient of determination was 92.0%. The correlation coefficient between the observed and the predicted body weight was positive and highly significant. It was concluded that sex, body condition, heart girth and breed are useful predictors of body weight of calves in the Maasai pastoral production system.